Conocimiento de Salud Oral entre Adolescentes de Población Urbana y Rural. - Cruz Lara, Brayan David (2026)
Introduction: According to the WHO, approximately 3.5 billion people suffer from oral diseases, with greater impact in rural areas. This study aimed to compare self-perceived oral health and knowledge of oral health care among adolescents from urban and rural areas of Riobamba, Ecuador. Methods: An observational, analytical, cross-sectional study was conducted. A structured questionnaire was administered to 153 students aged 12 to 14 years from four educational institutions selected through convenience sampling. Results: Urban adolescents reported more favorable perceptions of their teeth and gingival health, whereas rural participants more frequently described their oral status as “fair” and demonstrated greater lack of knowledge. Oral hygiene practices were better among the urban group, including higher use of dental floss and mouthwash. Urban adolescents also visited the dentist more frequently and with clearer reasons for consultation, while rural adolescents reported lower attendance and uncertainty regarding the purpose of their visits. Overall, oral health knowledge was significantly higher in the urban population. Conclusions: A marked urban–rural gap was observed in self-perception of oral health, hygiene practices, access to dental services, and oral health knowledge. These findings highlight the need for targeted educational and preventive strategies in rural areas to reduce inequalities and promote better oral health outcomes.